Association between resting heart rate and low natural killer cell activity: a cross-sectional study - Oh, Hyoju; Cho, A-Ra; Jeon, Joo-Hwan; Suh, Eunkyung; Moon, Junhyung; Cho, Baek Hwan; Lee, Yun-Kyong (Frontiers in Immunology, 2024)
Resting heart rate (RHR), a simple physiological indicator, has been demonstrated to be associated with inflammation and even metabolic disorders. This study aimed to investigate whether RHR is associated with natural killer cell activity (NKA) in a large population of healthy adults using a novel assay to measure NKA. This cross-sectional study included 7,500 subjects in the final analysis. NKA was estimated by measuring the amount of interferon-gamma (IFN-γ) released by activated natural killer cells; low NKA was defined as IFN-γ level <500 pg/mL. Subjects were categorized into four groups according to RHR as follows: C1 (≤ 60 bpm), C2 (60-70 bpm), C3 (70-80 bpm), and C4 (≥ 80 bpm). Individuals with higher RHR exhibited poorer metabolic and inflammatory profiles, with the prevalence of low NKA being highest in the highest RHR category. Compared with C1 as reference, the fully adjusted odd ratios (ORs) (95% confidence intervals (CIs)) for low NKA were significantly higher in C3 (OR: 1.37, 95% CI: 1.08-1.75) and C4 (OR: 1.55, 95% CI: 1.20-2.00). In addition, RHR was shown to exert indirect effects on NKA upon consideration of the mediation effect of serum cortisol in path analysis. Our findings confirm a significant link between elevated RHR and low NKA, and suggest the usefulness of RHR, a simple indicator reflecting increased sympathetic nervous system activity and stress, in predicting reduced immune function.